2017
DOI: 10.4269/ajtmh.16-0407
|View full text |Cite
|
Sign up to set email alerts
|

Household and Individual Risk Factors for Cholera among Cholera Vaccine Recipients in Rural Haiti

Abstract: Abstract.Oral cholera vaccination was used as part of cholera control in Haiti, but the vaccine does not provide complete protection. We conducted secondary data analyses of a vaccine effectiveness study in Haiti to evaluate risk factors for cholera among cholera vaccine recipients. Individuals vaccinated against cholera that presented with acute watery diarrhea and had a stool sample positive for Vibrio cholerae O1 were included as cases. Up to four vaccinated individuals who did not present for treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…The role of sex was evaluated in 15 studies [ 13 , 26 , 32 , 33 , 35 , 37 , 43 , 70 , 72 , 73 , 90 , 101 , 104 , 116 , 118 ], of which 11 implemented a multivariable model [ 32 , 33 , 35 , 37 , 72 , 73 , 90 , 101 , 104 , 116 , 118 ]. Seven of these studies met criteria for meta-analysis ( Supplementary Figure 1 ) [ 35 , 72 , 73 , 90 , 101 , 116 , 118 ]. The SOR for risk of cholera for females was 1.22 (95% confidence interval [CI], .71–2.12), with I 2 = 80% ( Q test P < .0001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of sex was evaluated in 15 studies [ 13 , 26 , 32 , 33 , 35 , 37 , 43 , 70 , 72 , 73 , 90 , 101 , 104 , 116 , 118 ], of which 11 implemented a multivariable model [ 32 , 33 , 35 , 37 , 72 , 73 , 90 , 101 , 104 , 116 , 118 ]. Seven of these studies met criteria for meta-analysis ( Supplementary Figure 1 ) [ 35 , 72 , 73 , 90 , 101 , 116 , 118 ]. The SOR for risk of cholera for females was 1.22 (95% confidence interval [CI], .71–2.12), with I 2 = 80% ( Q test P < .0001).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies evaluated household building materials [ 10 , 32 , 33 , 41 , 43 , 73 , 101 , 110 ]. Seven of these implemented multivariable models [ 10 , 32 , 33 , 41 , 73 , 101 , 110 ], 5 of which found that higher-quality housing was associated with lower risk of cholera [ 10 , 32 , 33 , 101 , 110 ]. One study found that risk of cholera independently increased with population density surrounding a household [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, communal sections in Haiti are largely unurbanized, therefore the incidence of cholera might be associated with different factors such as the practice of latrine sharing 26 .…”
Section: Resultsmentioning
confidence: 99%
“…In 53% of studies that assessed water-related exposures, there was at least one significant water-related exposure where the transmission domain could not be determined. This was most often because treating water (by boiling, chlorine or unspecified) in the home could eliminate contamination from either domain [8,39,49,50,52,56,58,68,76,78,86,87,94,96]. Several of these studies also presented evidence of significant public domain transmission, suggesting that even if household transmission could not be determined, public transmission was likely present [39,49,50,78,94].…”
Section: Resultsmentioning
confidence: 99%